Digital Database and Maps of Quaternary Deposits in East and Central Siberia - Robin N. Bryant; Joel E. Robinson; Maxwell D. Taylor; William Harper; Amy DeMasi; Emily Kyker-Snowman; Alexandra Veremeeva; Lutz Schirrmeister; Jennifer Harden; Guido Grosse (USGS Science Data Catalog, 2017)
This digital database is the product of collaboration between the U.S. Geological Survey, the Alfred Wegener Institute for Polar and Marine Research Potsdam, Foothill College GeoSpatial Technology Certificate Program, and the Geophysical Institute at the University of Alaska. The primary goal for creating this digital database is to enhance current estimates of organic carbon stored in deep permafrost, in particular Late Pleistocene syngenetic ice-rich loess permafrost deposits, called Yedoma. This deposit is vulnerable to thermokarst and erosion due to natural and anthropogenic disturbances. The original paper maps were issued by the Department of Natural Resources of the Russian Federation or its predecessor the Department of Geology of the Soviet Union and have their foundation in decades of geological field and remote sensing work and mapping at scales 1:50,000 to 1:500,000 by Russian geologists and cartographers in the respective regions. Eleven paper maps were scanned and digitized to record the geology unit boundaries, genetic type and clast size of each geologic unit, and borehole and outcrop locations. We also calculated area in km2, perimeter in km for each polygon. These attributes were used in support of (Grosse and others, 2013) which focused on extracting geologic units interpreted as Yedoma, based on lithology, ground ice conditions, geochronology, geomorphologic, and spatial association. Grosse, G., Robinson, J.E., Bryant, R., Taylor, M.D., Harper, W., DeMasi, A., Kyker-Snowman, E., Veremeeva, A., Schirrmeister, L., and Harden, J., 2013, Distribution of late Pleistocene ice-rich syngenetic permafrost of the Yedoma Suite in east and central Siberia, Russia: U.S. Geological Survey Open File Report 2013-1078, 37p. http://pubs.usgs.gov/of/2013/1078/ http://pubs.usgs.gov/of/2013/1078/pdf/ofr20131078.pdf